The tick salivary protein sialostatin L inhibits the Th9-derived production of the asthma-promoting cytokine IL-9 and is effective in the prevention of experimental asthma - Horka, Helena; Staudt, Valérie; Klein, Matthias; Taube, Christian; Reuter, Sebastian; Dehzad, Nina; Andersen, John F; Kopecky, Jan; Schild, Hansjörg; Kotsyfakis, Michalis; Hoffmann, Markus; Gerlitzki, Bastian; et al. (Journal of immunology (Baltimore, Md., 2012)
Ticks developed a multitude of different immune evasion strategies to obtain a blood meal. Sialostatin L is an immunosuppressive cysteine protease inhibitor present in the saliva of the hard tick Ixodes scapularis. In this study, we demonstrate that sialostatin L strongly inhibits the production of IL-9 by Th9 cells. Because we could show recently that Th9-derived IL-9 is essentially involved in the induction of asthma symptoms, sialostatin L was used for the treatment of experimental asthma. Application of sialostatin L in a model of experimental asthma almost completely abrogated airway hyperresponsiveness and eosinophilia. Our data suggest that sialostatin L can prevent experimental asthma, most likely by inhibiting the IL-9 production of Th9 cells. Thus, alternative to IL-9 neutralization sialostatin L provides the basis for the development of innovative therapeutic strategies to treat asthma.
Keywords: Animals; Enzyme-Linked Immunosorbent Assay; Female; Cytokines; průtoková cytometrie; ženské pohlaví; Mice, Knockout; myši knockoutované; cytokiny; Mice; Flow Cytometry; Cystatins; polymerázová řetězová reakce s reverzní transkripcí; Mice, Inbred BALB C; Ixodidae; Asthma; myši; Interleukin-9; separace buněk; ELISA; T-lymfocyty - podskupiny; Male; Reverse Transcriptase Polymerase Chain Reaction; modely nemocí na zvířatech; myši inbrední BALB C; bronchiální astma; interleukin-9; Disease Models, Animal; Cell Separation; T-Lymphocyte Subsets; zvířata; mužské pohlaví; cystatiny; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction